Pengaruh Budaya Organisasi dan Work Life Balance terhadap Kinerja Pegawai (Studi pada Wanita Pekerja di Jawa Timur) - Hikmah, Lailatul; Tama, Shallya Yudha (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
This research was conducted with the aim of analyzing the influence of organizational culture and work life balance on the performance of female employees in the East Java region. Data collection was carried out by observing and distributing questionnaires. The sampling technique in this study used purposive sampling with the criteria of women working in the East Java region. The number of samples used was 100 respondents who were working women in the East Java Region. The analysis tools used are multiple linear analysis test, coefficient of determination test, and hypothesis test. The results of this study indicate that: 1) organizational culture variables partially have a significant effect on employee performance, 2) work life balance variables partially have a significant effect on employee performance, 3) organizational culture and work life balance variables have a simultaneous effect on employee performance.